Aqueous extract of Andean berry (Vaccinium meridionale Swartz) promotes antiproliferative effect of 5–fluorouracil and leucovorin treatment with or without oxaliplatin and inhibits metastatic potential in colon adenocarcinoma cells (2023)
ABSTRACT: Objective: To determine the effect of the aqueous extract of Andean berry (Vaccinium meridionale Swartz) alone or in combination with 5–fluorouracil (5–FU), leucovorin (LEU), and oxaliplatin (OXA) on proliferation, adhesion, and metastatic potential in colon adenocarcinoma cell lines. Methods: Sulforhodamine B assay was used to evaluate cell viability, and crystal violet staining was employed to assess the adhesion and cloning efficiency of SW480 and SW620 cells. Commercial kits were used to evaluate the migration, invasion capacity, and levels of matrix metalloproteinases–2, –7, and –9 in the SW620 cell line. Results: The Andean berry extract (30% v/v) combined with the tested drugs showed a greater inhibitory effect on the viability of SW480 and SW620 cells than the drugs alone. The cloning efficiency of both cell lines was similar after treatment with drugs alone or combined with the extract. The extract decreased the adhesion of SW480 cells and also the migration and invasion of SW620 cells. Moreover, the drugs combined with the aqueous extract showed a greater inhibitory effect on the migration and invasion of SW620 cells than the drugs alone. The extract decreased the matrix metalloproteinase–9 (MMP–9) level of SW620 cells. Conclusions: The aqueous extract of Andean berry promoted the antiproliferative effect of the combination of 5–FU, LEU, and OXA in SW480 and SW620 cells while showing a potential antimetastatic effect in SW620 cells.